Information and Communication Technologies and Teacher Educators of English in Nepal (Journal of NELTA, 2018)
Nepal’s teacher education is witnessing a number of hurdles and the case has been deteriorating further. It is imperative to improve the existing situation with no delay. Regarding Information and Communication Technologies (ICTs), I have tried to figure out the present situation of knowledge, practice and expectations of the teacher educators of English working in both public/community and private teacher education institutions of Nepal. A survey was conducted using a questionnaire. A total of twenty-five informants fully responded to the questionnaire. It was found that they were aware of the need for including ICTs in classroom instruction but due to the resource constraints, lack of trainings and lack of readiness in the administrative systems, they have not been able to make use of ICTs in classroom instruction. Journal of NELTA, Vol 20 No. 1-2, December 2015, Page: 27-33